The Effectiveness of Playful Learning Design on Learning Outcomes and Cognitive Load in Junior High School Informatics - Hidayat, Febryanti; Hikmawan, Rizki; Nurul Hayati, Sayyidah (Jurnal Paedagogy, 2026)
This study aims to evaluate the effectiveness of pedagogical PSD adaptation in improving learning outcomes while managing junior high school students’ cognitive load in Informatics learning. This research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group pretest–posttest design. The sample consisted of 56 eighth-grade students who were divided into an experimental group implementing the PSD method and a control group using the Think Pair Share method. Data were collected through pretests, posttests, and cognitive load questionnaires. The data were analyzed using descriptive statistics to summarize learning outcomes, followed by the Shapiro–Wilk test to examine data normality. Since the posttest data were not normally distributed, the Mann–Whitney U test was conducted to compare learning outcomes between the experimental and control groups. Cognitive load was measured using a questionnaire based on Cognitive Load Theory (CLT) and analyzed descriptively through mean scores across three dimensions: intrinsic, extraneous, and germane cognitive load. The module review results indicated that the adapted PSD module was considered appropriate by six Informatics teachers in terms of content, language, and alignment with student characteristics. The statistical analysis revealed a significant difference between the two groups, with the experimental group achieving higher learning outcomes than the control group (p < 0.05). Regarding cognitive load, both groups demonstrated low intrinsic and extraneous cognitive loads, while the experimental group exhibited a higher germane cognitive load. These findings suggest that PSD adaptation effectively improves learning outcomes while promoting more optimal cognitive engagement among students in Informatics learning.